Дослідження методів оптимальної фільтрації шумів для розпізнавання зображень - Лавров, О. Є. (ХНУРЕ, 2023)
This work is devoted to the evaluation of image filtering methods and their application to increase the accuracy of object recognition in photos. Additionally, this study seeks to evaluate the strengths and weaknesses of each noisefiltering method and identify the optimal filtering parameters for each method. By exploring these factors, this work aims to provide a comprehensive understanding of the advantages and limitations of each filtering method and to identify the most effective approach for increasing the accuracy of object recognition in photos.